Inisiasi Kampung Wisata Bersih Dan Sehat Melalui Upaya Pencegahan Leptospirosis di Kampung Bustaman - Fitria Anggraini; Aprianti Aprianti (Jurnal Salam Sehat Masyarakat (JSSM), 2021)
Bustaman village is a village that has the potential for goat slaughter routines and the "gebyuran" tradition, this increases the potential for environmental health problems from piles of carcass waste from goats to piles of plastic waste, both of which can pollute the environment and cause potential zoonoses such as rats that can transmit diseases. leptospirosis. The method of implementing community service is carried out by empowering the community through a problem solving cycle approach. The first stage starts from problem identification, problem priority, brainstorming, village community deliberation and then intervention. The results of community service are quite good, the activities run smoothly as seen from the people who are active in identifying health problems, namely diseases that come from animals, namely rats, mosquitoes and flies. The priority of the community problem is the prevention of a rat-borne disease, namely leptospirosis. The intervention was carried out by catching rats and facilitated by the service team by distributing 20 mouse traps. The eradication of rats has been carried out and the community is committed to carrying out these activities continuously. It is hoped that the local health center can facilitate leptospirosis prevention activities by providing assistance to the community so that these activities can continue.